(3GdEfLjds
(3ChdgG (B:s
(3jYde ai eMGadge hjfGOi HTGQI hjTai cd Sbje hcd ESJQNGA ai GdTYH s
(3BNQgG (B:s
(3ef HYO bjGeJg ef GdehGJ hbGd TeYGf HWQS Je s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B175s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdOjGfGJ GdCNQis